2015
DOI: 10.1155/2015/747543
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Defenses in Human Tuberculosis: An Overview of the Interactions betweenMycobacterium tuberculosisand Innate Immune Cells

Abstract: Tuberculosis (TB) remains a serious global public health problem that results in up to 2 million deaths each year. TB is caused by the human pathogen, Mycobacterium tuberculosis (Mtb), which infects primarily innate immune cells patrolling the lung. Innate immune cells serve as barometers of the immune response against Mtb infection by determining the inflammatory milieu in the lungs and promoting the generation of adaptive immune responses. However, innate immune cells are also potential niches for bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 105 publications
0
100
1
11
Order By: Relevance
“…It is important to bear in mind that MHC-identical MCMs are not necessarily genetically identical outside the MHC, which may explain why our results contrast with the observation that monozygotic twin marmosets infected with the same strains of M. tuberculosis exhibited similar disease courses (36). In addition, the secretion of cytokines and presentation of antigens by macrophages, dendritic cells, or other innate cell types to initiate the adaptive immune response are well established to play a critical role in controlling M. tuberculosis replication and determining overall TB resistance (37)(38)(39). Ultimately, MHCmatched MCMs infected with the same dose and strain of M. tuberculosis may be valuable for defining non-MHC determinants of TB disease.…”
Section: Discussioncontrasting
confidence: 72%
“…It is important to bear in mind that MHC-identical MCMs are not necessarily genetically identical outside the MHC, which may explain why our results contrast with the observation that monozygotic twin marmosets infected with the same strains of M. tuberculosis exhibited similar disease courses (36). In addition, the secretion of cytokines and presentation of antigens by macrophages, dendritic cells, or other innate cell types to initiate the adaptive immune response are well established to play a critical role in controlling M. tuberculosis replication and determining overall TB resistance (37)(38)(39). Ultimately, MHCmatched MCMs infected with the same dose and strain of M. tuberculosis may be valuable for defining non-MHC determinants of TB disease.…”
Section: Discussioncontrasting
confidence: 72%
“…Mtb can be recognized by numerous receptors and induces a network of signaling pathways to drive inflammatory responses, involving toll-like receptors (TLRs), C-type lectins, Aryl hydrocarbon receptor (AhR), and Cyclic GMP-AMP synthase (cGAS). [34][35][36] Studies on gene expression profiles of Mtbinfected human macrophages provided the evidence for the importance of IL-1b and IL-12 in combating Mtb. 37 Importantly, one study identified CCL1, produced from macrophages of TB patients after Mtb stimulation, was involved in host susceptibility to TB.…”
Section: Discussionmentioning
confidence: 99%
“…These responses are an integral component of host defence and bacterial containment 34,43,44,61 , and they are intimately linked with granuloma outcome 37,6264 . The particular immune cells involved in TB immunity 34,6567 , and their localization and kinetics 32,41,61,68 , have been extensively reviewed in the past few years. Here, we discuss how the heterogeneity of the immune response in TB influences the local granuloma microenvironment.…”
Section: Granuloma Heterogeneitymentioning
confidence: 99%